KONTRIBUSI SEKTOR PARIWISATA DAN PERTUMBUHAN EKONOMI DI PROVINSI MALUKU - CHRESTIANA APONNO, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Tourism sector is a foreign exchange contributor sector for the country. Growing and advanced tourism will further boost economic growth in Indonesia. This study aims to find out the extent to which tourism potential in Maluku contributes to economic growth in Maluku.The method used is descriptive qualitative method by using secondary data source related to research issue. The results showed that the potential of a large tourism sector in Maluku has not been able to improve the welfare and economic growth of the people and regions of Maluku. This research provides enlightenment and motivation for the tourism industry of Maluku province to be more active in promoting tourism potentials in Maluku so as to increase economic growth of the Maluku region by increasing foreign exchange for the country. This research is also the basis of the local government especially the tourism office in setting policies related to the Maluku tourism industry and opening cooperation with the community and tourism sector entrepreneurs in the development of tourist attractions in Maluku.